States of matter - Discovery Channel School; Discovery Communications Inc. ([Bethesda, Md.] : Discovery Communications Inc., 2001)
Explains how everything on Earth can be grouped into four states of matter and how matter can change from one state to another by applying heat or pressure. Includes related activities
Teacher's guide in PDF and Microsoft Word format
System requirements : Windows 95/98, pentium processor 100 MHz and above, 16 MB installed RAM, minimum 25 MB free hard disc space, minimum resolution of 640 X 480, 16-bit color, 4 X CD-ROM drive
System requirements : Power PC macintoch at 100 MHz or better, running system 7.6.1 or higher, minimum of 8 Mb available RAM, minimum of 25 MB free had disc space, 640 X 480 resolutions, 16-bit color, 4 X multimedia-compliant CD-ROM drive
Keywords: Matter -- Properties -- Juvenile literature; Matter -- Properties